3D-printed poly(lactic acid) scaffolds for trabecular bone repair and regeneration: scaffold and native bone characterization. (4th May 2019) - Velioglu, Zeynep Busra; Pulat, Deniz; Demirbakan, Beril; Ozcan, Burak; Bayrak, Ece; Erisken, Cevat
ABSTRACT: Purpose : Study objectives were set to (i) fabricate 3D-printed scaffolds/grafts with varying pore sizes, (ii) characterize surface and mechanical properties of scaffolds, (iii) characterize biomechanical properties of bovine trabecular bone, and (iv) evaluate attachment and proliferation of human bone marrow mesenchymal stem cells on 3D-printed scaffolds. Materials and Methods : Poly(lactic acid) scaffolds were fabricated using 3D-printing technology, and characterized in terms of their surface as well as compressive mechanical properties. Trabecular bone specimens were obtained from bovine and characterized biomechanically under compression. Human bone marrow mesenchymal stem cells were seeded on the scaffolds, and their attachment capacity and proliferation were evaluated. Results : Contact angles and compressive moduli of scaffolds decreased with increasing pore dimensions of 0.5 mm, 1.0 mm, and 1.25 mm. Biomechanical characterization of trabecular bone yielded higher modulus values as compared to scaffolds with all pore sizes studied. Human bone marrow mesenchymal stem cells attached to the surfaces of all scaffolds yet proliferated more on scaffolds with 1.25 mm pore size. Conclusions : Collectively, given the similarity between 3D-printed scaffolds and native bone in terms of pore size, porosity, and appropriate mechanical properties of scaffolds, the 3D-printed poly(lactic acid) (PLA) scaffolds of this study appear as candidate substitutes for bone repair and regeneration.